Problems and Prospects of Sustainable Development of Supply Chain (Case Study: the EEU Countries) - Ð¢.Ð. Selishcheva; D.Iu. Miropolskii; S.A. Diatlov; Iu.V. Kuzminykh; A.V. Potapenko (International Journal of Supply Chain Management, 2018)
Abstract- This paper deals with the economies of the EEC member states in the context of the transition to sustainable development of supply chain. The subject of the study is to identify the problems of transition of the countries of the Eurasian Economic Union to sustainable development and determine their prospects. Research hypothesis: it is customary to consider sustainable development in terms of three aspects: economic, social and environmental. If we carry out a study of the degree of sustainability of the development of the EEU countries in these areas using the social stability index, the environmental efficiency index and the progress index for sustainable development goals, and then compare the results with the lead countries and global trends, then we can identify the main problems of the Eurasian countries in their transition to sustainable development of supply chain and propose a system of measures to address them. The objective of the study identify the problems of transition to sustainable development of the EEC countries and to outline the main ways to resolve them in the context of Eurasian integration. Research methods are evolutionary and systemic approaches, principles of formal logic, and comparative analysis of statistical data. The analysis of the economic, social and environmental aspects of the sustainable development of the EEU countries has led to the conclusion that environmental problems are the main constraint in the transition to sustainable development of supply chain. This is evidenced by indicators of environmental well-being, environmental performance ratings and the progress index on the sustainable development of supply chain goals of the Eurasian countries, which are much lower than those of the leading countries and average global values, and tend to decrease. We distinguished the directions for addressing environmental problems of the countries of the Eurasian Economic Union: increasing the balancing effectiveness of economic development with environmental sustainability; unifying environmental legislation; strengthening cooperation within the framework of the Eurasian technology platform